HOMME ET SON ENVIRONNEMENT : POUR QUEL RAPPORT? - Augustin, SOMBO Baelongandi; Kamoy, ASANGO; Gabriel, EKAKWA Ewolo; MOPINA, Alain MAKWATU MONGA (IJRDO - Journal of Social Science and Humanities Research, 2022)
This research shows the report between the man and the environment, because on the one hand, the man is a to be endowed with the reason and containing the stakes and the importance of the environment for his life and survival daily. Of where, he must adopt a very responsible behavior opposite the environment that constitutes a common heritage of the humanity and a common house for all living being. It is to this level that Hans Jonas, insist on the man’s co-responsibility managing the environment well presently in order to think about the future generation. On the other hand, the environment being considered like a wealth returns a non negligible service to the man on the plans social, economic, cultural, anthropological, politics, sanitary, educational.